Environmental Health with the Standardization of Air Ventilation Covid Radiology Examination Room-19 at Mardi Waluyo Hospital, Blitar City - Indasah; Pramono; Sri Rahayu (Journal for Quality in Public Health, 2023)
Air as an important environmental component in life needs to be maintained so that the quality of health is always excellent. Poor air ventilation and high concentrations of aerosols are one of the transmissions of COVID-19, therefore WHO has issued guidelines for regulating hospital air conditioning, while Permenkes RI No.07 of 2019 requires quality standards for environmental health and hospital health including: water; air; etc. The Radiology Installation includes supporting services for examining COVID-19 patients, with minimal air ventilation requiring environmental health studies. Knowing the air system, especially the air ventilation system in the radiology examination room for COVID-19 at Mardi Woluyo Hospital, Blitar City, in the context of improving public health. Observation, interviews, problem identification, socialization of results and recommendations for improvement, with instruments fishbone diagrams, ultrasound and SWOT analysis. Radiology examination room for COVID-19 = p 4.80 x l 4.25 x h 3.50 m, door 1.8 X 2 m without windows, using Split HVAC (AC) system 2.5 PK, average daily temperature 220C and humidity < 60%, no air intake from the outside, ventilation with a portable HEPA air purifier Medina / type - T 1000 system with a coverage area of ​​120 m3, Air Flow Max=1000 m³/hour and there is no procedure shutdown time. In calculating the max ACH ability of this tool 14.17 times / hour so it requires shutdown time 19.5 minutes to restore its air quality. The COVID-19 Radiology Room at Mardi Waluyo Hospital, Blitar City, is used as a room for X-photo examination of COVID- and Non-COVID patients, allowing aerosol spread to occur in that room and this requires further study.